Recommendations for Resolving Community and Company Land Conflicts in Riau Province - Zulfikri Zulfikri (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
The land development process carried out by the company in recent decades has caused many conflicts with the community. It is undeniable that Riau Province is one of the eight provinces in Sumatra located in the eastern part which is mostly lowland with the potential for natural resources, especially in the field of plantations and forestry which makes oil palm plantation companies build many mills, control and develop land into plantations. Through the analytical descriptive method, situations and phenomena that become conflicts are presented, especially the causes and efforts to resolve the conflict. Some of the conflicts that occurred were given recommendations for alternative resolutions including; in the form of a study of government policies on right-to-use permits, mapping forest and plantation areas to obtain clear boundaries, eliminating the basis of conflict from their actions in conflict, victory of one party and defeat on the other, compromise, peace and impossibility of reconciliation, intensifying mediation between conflicting parties and the application of religious teachings as an effort so that the intensity and duration of conflict can be reduced or even can be reduced, especially conflicts that have been going on for a long time due to the repetition of previous conflicts.